Limonoids from seeds of Azadirachta indica A. Juss. and their cytotoxic activity - Jian Chen; Xiaona Fan; Jianhua Zhu; Liyan Song; Zhiwei Li; Fei Lin; Rongmin Yu; Hanhong Xu; Jiachen Zi (Elsevier, 2018)
Four new limonoid-type nortriterpenoids, 1-detigloyl-1-O-methacryloylsalannin (1), 28-deoxo-2,3-dihydronimbolide (2), 12-acetoxy-3-O-acetyl-7-O-tigloylvilasinin (3) and 12-acetoxy-3-O-acetyl-7-O-methacryloylvilasinin (4), along with five known ones, were isolated from seeds of Azadirachta indica A. Juss. Their structures were elucidated by various spectroscopic methods, including UV, IR, MS, NMR, X-ray crystallography, quantum chemical calculation, as well as by comparison of their spectroscopic data with those reported. In the in vitro cytotoxic assay, 2 showed inhibitory activity against human breast cancer MDA-MB-231 cell line with IC50 value of 7.68±1.74 μmol/L, and 5 inhibited growth of human cervical cancer Hela cell line, melanoma A375 cell line and promyelocytic leukemia HL-60 cell line, with IC50 12.00±2.08, 17.44±2.11, and 13.95±5.74 μmol/L, respectively. KEY WORDS: Azadirachta indica, Nortriterpenoid, Limonoid, Spectroscopy, Cytotoxic activity